Znaczenie aktywności fizycznej dla człowieka w samoocenie uczestników zajęć w klubie „Maximus” w Bydgoszczy = The importance of physical activity for human participants self-assessment classes at the club "Maximus" in Bydgoszcz - Lisiak, Dorota; Napierała, Marek; Pezala, Małgorzata; Zukow, Walery (Journal of Education, Health and Sport, 2015)
Lisiak Dorota, Napierała Marek, Pezala Małgorzata, Zukow Walery. Znaczenie aktywności fizycznej dla człowieka w samoocenie uczestników zajęć w klubie „Maximus” w Bydgoszczy = The importance of physical activity for human participants self-assessment classes at the club "Maximus" in Bydgoszcz. Journal of Education, Health and Sport. 2015;5(1):151-162. ISSN 2391-8306. DOI: 10.5281/zenodo.14759 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A151-162 https://pbn.nauka.gov.pl/works/532880 http://dx.doi.org/10.5281/zenodo.14759 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.01.2015. ZNACZENIE AKTYWNOŚCI FIZYCZNEJ DLA CZŁOWIEKA W SAMOOCENIE UCZESTNIKÓW ZAJĘĆ W KLUBIE „MAXIMUS” W BYDGOSZCZY THE IMPORTANCE OF PHYSICAL ACTIVITY FOR HUMAN PARTICIPANTS SELF-ASSESSMENT CLASSES AT THE CLUB "MAXIMUS" IN BYDGOSZCZY Dorota Lisiak, Marek Napierała, Małgorzata Pezala, Walery Zukow Uniwersytet Kazimierza Wielkiego w Bydgoszczy Kazimierz Wielki University, Bydgoszcz, Poland Słowa kluczowe: zdrowy styl życia, aktywność fizyczna. Keywords: healthy lifestyle, physical activity. Abstract The main objective of this study was to present the special benefits of physical activity among participants of the club "Maximus" in Bydgoszcz. The study was conducted using a diagnostic survey using the tools research survey of 69 women and 48 men. Specific objectives: 1. What does the phrase "healthy lifestyle"? 2. How do people spend their free time? 3. What motivates a man to sport? 4. What restricts participation in classes in fitness clubs? conclusions: • A healthy lifestyle is associated primarily with physical activity, healthy food, • Limited financial resources and little free time are the main factors limiting the frequency of visiting fitness clubs, • Admission is a major issue that affects the choice of club, • The main factors motivating physical activity is a desire to improve the figure and the desire to lose the extra pounds, • Interest in the environment of people attending the club Maximus classing on average. Streszczenie Celem głównym badań było przedstawienie korzyści jakie niesie aktywność fizyczna wśród uczestników klubu „Maximus” w Bydgoszczy. Badania zostały przeprowadzone za pomocą sondażu diagnostycznego z wykorzystaniem narzędzia badawczego- ankiety, wśród 69 kobiet oraz 48 mężczyzn. Cele szczegółowe: Co oznacza formuła „zdrowy styl życia”? W jaki sposób ludzie spędzają czas wolny? Co motywuje człowieka do uprawiania sportu? Co ogranicza uczestnictwo w zajęciach w klubach fitness? Wnioski: Zdrowy styl życia utożsamiany jest głównie z aktywnością fizyczną, zdrową żywnością, Ograniczone środki finansowe i mało czasu wolnego są głównymi czynnikami ograniczającymi częstotliwość odwiedzania klubów fitness, Cena wstępu stanowi główny aspekt wpływający na wybór klubu fitness, Głównymi czynnikami motywującymi do uprawiania aktywności fizycznej są chęć poprawy sylwetki oraz chęć zgubienia zbędnych kilogramów Zainteresowanie w środowisku ludzi uczęszczających do klubu Maximus klasuje się na średnim poziomie.